2020
DOI: 10.1177/1455072520905404
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol intakes before and during pregnancy: Impact on the mother and infant outcome to 18 months

Abstract: Aim: To investigate maternal alcohol intakes before and during pregnancy, their impact on mothers and infants to 18 months. Method: Prospective study of 504 New Zealand volunteers visited in months 4 and 7 of pregnancy, measurements taken, lifestyle details recorded including alcohol intake before and during pregnancy. Eighteen months after birth, 370 infants were measured, and infant development recorded. Results: Nineteen per cent of mothers never drank, 53% stopped when they knew they were pregnant, 29% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The significant association of frequent tella drinking events during pregnancy with stunting in the present study was consistent with a study in New Zealand, which assessed maternal alcohol intakes before and during pregnancy and reported their association with child growth restriction among children (4) . Another study also demonstrated the association of prenatal alcohol exposure with intrauterine growth restriction and suggested that this effect might persist well into early adulthood (33) .…”
Section: Discussionsupporting
confidence: 92%
“…The significant association of frequent tella drinking events during pregnancy with stunting in the present study was consistent with a study in New Zealand, which assessed maternal alcohol intakes before and during pregnancy and reported their association with child growth restriction among children (4) . Another study also demonstrated the association of prenatal alcohol exposure with intrauterine growth restriction and suggested that this effect might persist well into early adulthood (33) .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies show PAE before pregnancy is associated with other aspects of child developments, and the association is explained by maternal metabolic disorders such as impaired maternal glucose homeostasis and hepatic steatosis. [31][32][33] The mechanism of the association with the face could be similar, but further investigations are needed to test this.…”
Section: Discussionmentioning
confidence: 99%
“…While evidence has been conflicting regarding the association between alcohol diagnosis prior to and during pregnancy and risk of adverse birth outcomes, one prospective cohort of 1303 pregnant women in the United Kingdom found that intakes of more than 2 units of alcohol/week before pregnancy, and in trimesters 1 and 2, were significantly associated with increased risk of babies with lower birth weight, lower birth centile, and preterm birth compared to non-drinkers [ 17 ]. Likewise, in a recent animal study in South Korea, alcohol consumption before or during pregnancy was associated with increased risk of abnormal fetal development in ethanol-fed mice, who not only had significantly decreased growth rates during the lactation period, but postnatal macrosomia [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study found that parental binge drinking before conception may be associated with a baby’s congenital heart defects [ 14 ], possibly because alcohol exposure affects the DNA in developing sperm [ 15 ]. Another study claimed that alcohol intake before and during pregnancy is not associated with infant motor development, and is only slightly associated with mean infant weight, length, and head circumference at birth [ 16 , 17 ]. Because such studies are still new, there is no evidence concerning the effects of a previous alcohol diagnosis on adverse birth outcomes, especially for a nationwide population-based cohort.…”
Section: Introductionmentioning
confidence: 99%